Neuropsychopharmacology and therapeutics - Ebenezer, Ivor S. (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2015)
'Neuropsychopharmacology is a relatively new subject area in the neurosciences. It is a field of study that describes the effects of drugs from the molecular to the behavioural level and requires integration and synthesis of knowledge from various disciplines including neuroanatomy, physiology, molecular biology, pharmacology and the behavioural sciences. The principal aims of this book are to provide students with a clear understanding of CNS disorders, and an appreciation of how basic and clinical research findings can be translated into therapeutics. After an introduction to the subject area, the remaining chapters are focused on reviewing the main psychiatric and neurological disorders that are covered in most courses. They are discussed in terms of their clinical symptoms, epidemiology, pathology, aetiology, underlying neurobiological and neurochemical mechanisms, pharmacotherapy, adjunctive non-pharmacological treatments, and clinical outcomes. Each chapter of the book is a'stand-alone' chapter and is written in a clear, accessible style. Written by an author with many years teaching and research experience, this textbook will prove invaluable for students of pharmacology, pharmacy and the medical sciences needing a truly integrated introduction to this exciting field'--Provided by publisher.
Includes bibliographical references and index.
Machine generated contents note: Preface Chapter1. Introduction to Neuropsychopharmacology Chapter 2. Parkinson's Disease Chapter 3. Memory, Dementia and Alzheimer's Disease Chapter 4. Epilepsy Chapter 5. Attention Deficit Hyperactivity Disorder (ADHD) Chapter 6. Affective Disorders 1:Depression Chapter 7. Affective Disorders 2: Bipolar Disorders Chapter 8. Anxiety Disorders Chapter 9. Sleep and Sleep Disorders Chapter 10. Schizophrenia Chapter 11. Drug Abuse and Misuse Index.
Keywords: Neuropsychopharmacology; Therapeutics; Central Nervous System Agents -- therapeutic use; Central Nervous System Diseases -- drug therapy; Central Nervous System -- drug effects; Mental Disorders -- drug therapy; Neuropharmacology -- methods